A phylogenomic- and proteomic investigation into the evolution and biological characteristics of the members of the group 2 Latin-American Mediterranean (LAM) genotype of Mycobacterium tuberculosis - Dippenaar, Anzaan (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.